Metaphor in Ossetian Literary-Critical Text - R. G. Tsopanova; F. A. Tsarikaeva; E. S. Kachmazova (Научный диалог, 2024)
The article is dedicated to the study of metaphor as a means of forming scientific concepts and creating expressive-illustrative context. The research aims to identify types and sources of metaphorical transfers in Ossetian literary-critical texts and analyze their functioning as an important part of the language of these texts. The novelty of this study lies in the first-ever analysis of metaphor types in Ossetian literary-critical texts, verbalizing scientific concepts and creating an expressive field specific to scientific discourse. Sources of metaphors and their functions are identified. The study reveals that the main types of metaphors in the language of the texts under investigation are nominative, figurative, poetic (individual), and cognitive. Sources of metaphors include nature-mimetic and anthropocentric, acoustic, visual, and spatial groups, artifacts, symbols, etc. Metaphors are integrated into the content of the texts as essential linguistic material capable of creating a scientific context and reflecting the scientific worldview of the people. Many scientific concepts and a range of artistic-illustrative means in the analyzed texts can be considered borrowings from the Russian language, indicating a connection between the two languages in the scientific sphere of communication.